A probabilistic framework for comparison of dam breach parameters and outflow hydrograph generated by different empirical prediction methods. (December 2016) - Ahmadisharaf, Ebrahim; Kalyanapu, Alfred J.; Thames, Brantley A.; Lillywhite, Jason
Abstract: This study presents a probabilistic framework to simulate dam breach and evaluates the impact of using four empirical dam breach prediction methods on breach parameters (i.e., geometry and timing) and outflow hydrograph attributes (i.e., time to peak, hydrograph duration and peak). The methods that are assessed here include MacDonald and Langridge-Monopolis (1984), Von Thun and Gillette (1990), Froehlich (1995), 2008). Mean values and percentiles of breach parameters and outflow hydrograph attributes are compared for hypothetical overtopping failure of Burnett Dam in the state of North Carolina, USA. Furthermore, utilizing the probabilistic framework, the least and most uncertain methods alongside those giving the most critical value are identified for these parameters. The multivariate analysis also indicates that lone use of breach parameters is not necessarily sufficient to characterize outflow hydrograph attributes. However, timing characteristic of the breach is generally a more important driver than its geometric features. Highlights: A probabilistic dam breach model for overtopping is presented in this study. Uncertainty of breach parameters and outflow hydrograph is estimated. Four empirical dam breach prediction methods by using this model are compared in this study.